Continuous improvement in primary school performance: the role of quality management in vision and mission development - Sopandi Sopandi; R. Supyan Sauri; Usep Suherman (At Turots: Jurnal Pendidikan Islam, 2025)
School performance is one of the main factors in determining the quality of education. Primary schools as basic education institutions have an important role in shaping the character and competence of students. Therefore, the implementation of quality management in the preparation of the school's vision and mission is a major aspect in an effort to improve overall school performance. The implementation of quality management in the preparation of the vision and mission aims to ensure continuous planning, implementation, evaluation and improvement so as to achieve better educational standards. This study aims to analyze the impact of quality management in the preparation of vision and mission on improving primary school performance. The research method used is qualitative with a case study approach at SD Negeri Cimalati, Karangtengah District, Cianjur Regency, West Java. Data were collected through in-depth interviews, observations, and documentation studies. The data collected was then analyzed using data reduction, data presentation, and conclusion drawing techniques, while triangulation was used as a validation technique. The theoretical foundation in this study refers to the concept of quality management according to Deming, which emphasizes the importance of the quality planning cycle, quality implementation, quality evaluation, and quality follow-up. The results showed that the implementation of the vision and mission at SD Negeri Cimalati was carried out systematically through planning, implementation, evaluation, and continuous follow-up. The implementation of the vision and mission is accompanied by socialization to all school members, organization of resources, and continuous monitoring. Periodic evaluation allows for continuous improvement in the implementation of the school's vision and mission. The conclusion of this study confirms that the implementation of quality management in the preparation of school vision and mission has a significant impact on improving primary school performance. With a well-designed and consistently implemented vision and mission, schools can more easily achieve the set educational goals. In addition, the active participation of all stakeholders in the preparation and implementation of the school vision and mission also contributes to increasing the commitment and motivation of all school elements to continuously improve the quality of education. Therefore, this study recommends that other primary schools